1988
DOI: 10.1073/pnas.85.19.7302
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate regulation of two genes encoding gluconeogenic enzymes by the trans-dominant locus Tse-1.

Abstract: Tissue-specific extinguisher-i (Tse-1) is a mouse genetic locus that can repress liver-specific tyrosine aminotransferase gene expression in trans. To search for other Tse-l-responsive genes, hepatoma microcell hybrids retaining mouse chromosome 11 or human chromosome 17, containing murine Tse-1 and human TSEI, respectively, were screened for expression of liver-specific mRNAs. While most liver gene activity was unaffected in such hybrids, phosphoenolpyruvate carboxykinase and tyrosine aminotransferase gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…This led to the definition of tissue-specific extinguisher loci (reviewed in [166]). The Tse-J locus is responsible for the extinction of the PEPCK, tyrosine aminotransferase and aldolase B genes in hybrid cells [167]. The product of the Tse-J locus is the regulatory subunit RIa of PKA [168,169].…”
Section: Discussionmentioning
confidence: 99%
“…This led to the definition of tissue-specific extinguisher loci (reviewed in [166]). The Tse-J locus is responsible for the extinction of the PEPCK, tyrosine aminotransferase and aldolase B genes in hybrid cells [167]. The product of the Tse-J locus is the regulatory subunit RIa of PKA [168,169].…”
Section: Discussionmentioning
confidence: 99%
“…Clone 7AE-27 retains several human chromosome 17 markers including human 7&e-l. 7AD-7 retains a subset of these markers but is Tse-l- (Lem et al, 1988). Interestingly, several a/f-responsive genes are responsive to the presence of Tse-7 (Figure 6, compare lanes 1 and 5).…”
Section: Expressionmentioning
confidence: 96%
“…Extinction has been shown to have a specific genetic basis (Killary and Fournier, 1984). For example, it has been shown that the presence of a segment of human chromosome 17 is sufficient to extinguish TAT and PEPCK expression in rat hepatoma cells, suggesting that a single genetic locus, denoted Be-7 (tissue-specific extinguisher l), is responsible for extinction of these genes (Lem et al, 1988). Since TAT and PEPCK both require a/f for liverspecific expression, we hypothesized that other genes affected by a/f might also be regulated by Tse-1.…”
Section: Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of microcell hybrids containing parts of the long arm of fibroblast-derived human chromosome 17 in a hepatoma cell background have defined an extinguisher locus that influences many or possibly all cAMPregulated liver functions, including expression of the tyrosine aminotransferase (TAT) and phosphoenol pyrurate carboxykinase (PEPCK) genes (TSE1; Killary and Fournier 1984;Lem et al 1988;Thayer and Fournier 1989;Ruppert et al 1990). Recently, we identified a cAMP response element (CRE) in a liver-specific enhancer of the TAT gene as the target of TSEl-dependent extinction ) and, subsequently, showed TSE1 to be the regulatory subunit Rim of protein kinase A (Boshart et al 1991a;Jones et al 1991).…”
mentioning
confidence: 99%